Pengaruh Kompetensi dan Pelatihan Kerja Terhadap Kinerja Karyawan di Unit Kerja Sekertariat Deputi Kementerian Koperasi dan UKM - Suhardoyo Suhardoyo; Hadi Musyaffa (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
The background of this research is competence and training on employee performance. This study aims to determine whether there is an influence of Competency and Job Training on Employee Performance, especially in the Secretariat Work Unit of the Deputy Ministry of Cooperatives and SMEs. This study uses quantitative methods with an associative approach. The population in this study was all employees, totaling 40 people. The number of samples in this study was 40 respondents. The data collection technique in this study was by observing and using questionnaires which were distributed to employees specifically the Secretariat Work Unit Deputy of the Ministry of Cooperatives and SMEs. Data analysis techniques used validity test, reliability test, multiple linear analysis test, f-test, t-test, coefficient of determination, multicollinearity test, normality test, and heteroscedasticity test. Data processing in this study uses SPSS 24 for Windows. The results of this study prove that partially the Competency variable affects Employee Performance, while Training does not affect Employee Performance. Then simultaneously there is a significant influence between Competence and Training on Employee Performance, especially the Work Unit of the Deputy Secretariat of the Ministry of Cooperatives and SMEs